2014
DOI: 10.1021/jp408979h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Structure of Nitrogen-Doped Graphene with Single Platinum Atoms and Atomic Clusters as a Platform for the PEMFC Electrode

Abstract: A platform for producing stabilized Pt atoms and clusters through the combination of an N-doped graphene support and atomic layer deposition (ALD) for the Pt catalysts was investigated using transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM). It was determined, using imaging and spectroscopy techniques, that a wide range of N-dopant types entered the graphene lattice through covalent bonds without largely damaging its structure. Additionally and most notably, Pt atoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 56 publications
4
111
1
Order By: Relevance
“…[12][13] Botton et al, also reported the formation of a mixture of Pt atoms and clusters on the N-doped graphene support using Pt ALD. 14 Selective hydrogenation of 1,3-butadiene in an excess of alkenes is an important industrial process to purify the alkenes streams from petroleum cracking. 15 The critical requirements in this process are: (i) to achieve high selectivity to butenes, especially to 1-butene (the most desirable product) at high conversions; (ii) to minimize hydrogenation of the alkenes streams at high conversions; (iii) to achieve long durability against deactivation via carbonaceous deposits formation.…”
Section: Supporting Informationmentioning
confidence: 99%
“…[12][13] Botton et al, also reported the formation of a mixture of Pt atoms and clusters on the N-doped graphene support using Pt ALD. 14 Selective hydrogenation of 1,3-butadiene in an excess of alkenes is an important industrial process to purify the alkenes streams from petroleum cracking. 15 The critical requirements in this process are: (i) to achieve high selectivity to butenes, especially to 1-butene (the most desirable product) at high conversions; (ii) to minimize hydrogenation of the alkenes streams at high conversions; (iii) to achieve long durability against deactivation via carbonaceous deposits formation.…”
Section: Supporting Informationmentioning
confidence: 99%
“…[31][32][33][34] Although the ALD methodh as been employedi n variouse nergy-storage applications, such as LIBs, fuel cells, and lithium-sulfur batteries, coating of metal oxides on SIB cathodesw ith ALD has not yet been explored. [33,[35][36][37][38] Han et al reported the ALD of an Al 2 O 3 thin film on an Sn nanostructured anode for SIBs, along with improved cycling performance. [39] However,t he use of ALD metal-oxide coatings for SIB cathodes has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we need to discover an effective means to synthesize this ideal single-atom catalyst. In this paper, the atomic layer deposition (ALD) technique was utilized, as it has been proven to be a powerful tool for large-scale synthesis of stable single-atom and cluster catalysts1924. ALD has the ability to precisely control the size and distribution of particles on a substrate by using sequential and self-limiting surface reactions252627.…”
mentioning
confidence: 99%